2017
DOI: 10.1590/1519-6984.07116
|View full text |Cite
|
Sign up to set email alerts
|

Parasitism by a Digenea in Lucina pectinata (Mollusca: Lucinidae)

Abstract: Lucina pectinata is an important economic resource in the Brazilian coast. This study reports parasitism caused by a Digenea in this species. The specimens (n = 470) were collected in December 2012 in a mangrove swamp of the Cachoeira River estuary, Bahia, Brazil. They were measured along the anterior-posterior axis (length), and after macroscopic analysis for parasites and diseases cuts of 5 mm were fixated in Carnoy's solution and processed by routine histology technique wherein sessions of 7 μm were stained… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…High concentrations of sporocysts and cercariae were also responsible for infection of the gonads and also affected the gonadal follicles in Crassostrea rhizophorae up to 100% of prevalence (Brandão, et al, 2013). Studies of Bucephalus in bivalves on the Brazilian coast confirmed that when present at high intensities, sex determination is impossible (Garcia and Magalhães, 2008;Ceuta and Boehs, 2012;Ribeiro et al, 2018).…”
Section: Discussionmentioning
confidence: 98%
“…High concentrations of sporocysts and cercariae were also responsible for infection of the gonads and also affected the gonadal follicles in Crassostrea rhizophorae up to 100% of prevalence (Brandão, et al, 2013). Studies of Bucephalus in bivalves on the Brazilian coast confirmed that when present at high intensities, sex determination is impossible (Garcia and Magalhães, 2008;Ceuta and Boehs, 2012;Ribeiro et al, 2018).…”
Section: Discussionmentioning
confidence: 98%